A School-Based Study on Menstrual Hygiene Practices among Adolescent Girls in Ambala, Haryana - Ms. Alisha Sandhu; Ms Tanzin Angmo (The Bioscan, 2026)
Introduction: Adolescence is a critical transitional period marked by significant physiological and psychological changes, and menstruation is an important aspect of an adolescent girl’s reproductive health. Proper menstrual hygiene practices during this stage are essential for maintaining health and well-being. Methods: A descriptive research design was adopted to assess the expressed practices of menstrual hygiene among 100 adolescent girls studying in selected schools of Ambala, namely Duliana Government Senior Secondary School and D.A.V. Centenary Public School, Barara. Purposive sampling technique was used, and data were collected using a socio-demographic questionnaire and a self-structured menstrual hygiene practice checklist.